Meningkatkan Kemandirian Belajar Pak Pada Siswa Dengan Model PBL Pada Materi Maria Dan Elisabeth Menaggapi Rencana Allah Di Kelas V SDN 46 Plasma II - Melania Melanita (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education in Indonesia faces various complex challenges. Therefore, efforts continue to be made by the government, educational institutions and society as a whole to improve access, quality and relevance of education in order to create a young generation that is skilled, competitive and ready to face global challenges. In the context of the Independent Curriculum, Catholic religious education in Indonesia focuses on developing religious understanding, moral values ​​and Catholic spirituality for students. The independent curriculum emphasizes the Pancasila student profile. In this classroom action research, the researcher focuses on the dimension of independence which is based on the importance of forming strong character and mental attitudes in the younger generation, especially in facing complex global challenges. The students who are accepted to school at SD Negeri 46 Plasma II are students who are accepted into majors that do not match their initial interests. Students with this kind of condition tend to feel unmotivated to learn. Based on the problem conditions above, teachers can provide learning experiences by designing the learning process. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning. The objectives of the research include (1) to find out how the use of the Problem Based Learning model in increasing students' learning motivation in the material Maria and Elisabeth responded to God's plan in class V of SD Negeri 46 Plasma II, (2) to find out the increase in learning motivation of class V students of SD Negeri 46 Plasma II with the help of the Problem Based Learning model on Maria and Elisabeth material responding to God's plan, (3) to find out the use of the Problem Based Learning model on material for men and women equally, class V students at SD Negeri 46 Plasma II can apply the student profile Pancasila dimension of independence. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. The use of the Problem Based Learning model according to the syntax which includes orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, is effective in helping increase learning motivation and student independence in material Maria and Elisabeth responded to God's plan in class V of SD Negeri 46 Plasma II.